Granulomatous anterior uveitis with hypopyon in quiescent ulcerative colitis - Harshitha, K.; Pathengay, Avinash; Kelgaonkar, Anup; Patel, Anamika (Journal of Clinical Ophthalmology and Research, 2025)
We report a rare case of granulomatous anterior uveitis with hypopyon in a 31-year-old male with quiescent ulcerative colitis. Despite the absence of active gastrointestinal symptoms, the patient presented with acute visual loss and marked anterior chamber inflammation, including fibrin, hypopyon, and an iris nodule. Prompt initiation of topical therapy led to rapid resolution of inflammation and full visual recovery within a week. While extraintestinal manifestations are recognized in inflammatory bowel disease, anterior uveitis-particularly of a granulomatous nature with hypopyon-is uncommon in ulcerative colitis. This case underscores the importance of recognizing ocular complications even during systemic remission.